Peningkatan Mutu Dan Efisiensi Pelayanan Kesehatan Melalui Implementasi Rekam Medis Elektronik di Rumah Sakit - Asti Nurhayati; Ummu Muti’ah; Yuniarti Yuniarti (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Background Hospitals are health service facilities that have the most complex, capital-intensive and technology-intensive facilities and running hospitals tends to require expensive technology and large amounts of capital. The benefits of using electronic medical records are not only administrative benefits. The benefit felt by doctors and health workers is the ease of accessing patient information which ultimately helps in making clinical decisions. The use of electronic medical records has the potential to provide great benefits for health services such as basic and referral (hospital) service facilities. One of the benefits felt after using electronic medical records is increasing the availability of electronic patient records in hospitals. This is also beneficial for patients because it increases efficiency in the health care process. The aim of this community service activity is so that hospitals can implement electronic medical records to improve the quality and efficiency of health services. The method used in this service activity is outreach regarding the use of electronic medical records. The result of this community service activity is that users of electronic medical records in hospitals better understand how to use ERM and are able to improve the quality and efficiency of health services.